Safety profile of semagacestat, a gamma-secretase inhibitor: IDENTITY trial findings. (October 2014) - Henley, David B.; Sundell, Karen L.; Sethuraman, Gopalan; Dowsett, Sherie A.; May, Patrick C.
Abstract Objective: Semagacestat, a γ-secretase inhibitor, demonstrated an unfavorable risk–benefit profile in a Phase 3 study of patients with Alzheimer's disease (IDENTITY trials), and clinical development was halted. To assist in future development of γ-secretase inhibitors, we report detailed safety findings from the IDENTITY study, with emphasis on those that might be mechanistically linked to γ-secretase inhibition. Research design and methods: The IDENTITY trial was a double-blind, placebo-controlled trial of semagacestat (100 mg and 140 mg), in which 1537 patients age 55 years and older with probable Alzheimer's disease were randomized. Treatment-emergent adverse events (TEAEs) are reported by body system along with pertinent laboratory, vital sign, and ECG findings. Results: Semagacestat treatment was associated with increased reporting of suspected Notch-related adverse events (gastrointestinal, infection, and skin cancer related). Other relevant safety findings associated with semagacestat treatment included cognitive and functional worsening, skin-related TEAEs, renal and hepatic changes, increased QT interval, and weight loss. With few exceptions, differences between semagacestat and placebo treatment groups were no longer significant after cessation of treatment with active drug. Conclusions: Many of these safety findings can be attributed to γ-secretase inhibition, and may be valuable to researchers developing γ-secretase inhibitors.